Pembinaan Ekonomi GMIT Jemaat Bet’el Maulafa dan Jemaat Bethani Naet - Seu, Windynia (Institut Agama Kristen Negeri Palangka Raya, 2024)
The coaching of congregation is one of the church's tasks. The task of the church is to empower the congregation so that the congregation is more empowered to be able to meet their needs, both physical and spiritual. For this reason, this research was conducted to examine congregational empowerment at GMIT Berthany Naet Congregation and GMIT Bethel Maulafa Congregation. The research method used was descriptive qualitative and research information was obtained through Focus Group Discussion (FGD). From the results of the study, the economic empowerment of congregations at GMIT Bethany Na'et Congregation and GMIT Bethel Maulafa Congregation has an impact on the congregation's economy. Apart from having an impact on the congregation's economy, the economic empowerment of congregations at GMIT Bethel Maulafa Congregation and GMIT Naet Congregation also has an impact on agrotourism and congregation education. The empowerment of GMIT Bethel Maulafa Congregation and GMIT Congregation Na'et is driven by the church and funded from the congregation's treasury which is managed by the church.